Slimy stones and philosophy: some interpretations of tohu wa-bohu - Töyrylä, Hannu (Nordisk judaistik/Scandinavian Jewish Studies, 2000)
The creation account in the first chapter of Genesis tells us how, from this state called tohu wa-bohu in Hebrew, God created and formed the world in the course of six days. To this is added a mythical statement, probably by a Babylonia Amora, Rav, about tohu as a green line encircling the world and bohu as wet stones immersed deep in water. During centuries, the Jews became exposed to philosophy and science which were built on Greek heritage. Almost a thousand years after Rav, Abraham bar Hiyya, a Spanish astronomer, presented tohu and bohu as identical to the Aristotelian matter and form. Jewish thinkers were sometimes discussing the physical reality, sometimes the divine reality, sometimes both. Tohu and bohu, which in the beginning were empty, without value and next to nothing, had grown to be the roots of being, the secret of knowledge both physical and divine.